2012
DOI: 10.1111/j.1348-0421.2012.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase activity of Helicobacter pylori per se from 158 clinical isolates and the characteristics

Abstract: We investigated the correlation between the SOD activity of Helicobacter pylori (H. pylori) and gastroduodenal diseases and the characteristics of strains exposed to oxidative stress. Two sequenced strains, 26695 and J99, and clinical isolates from 156 Japanese patients with gastroduodenal diseases such as gastric cancer (n = 59) and non-cancer (n = 97) were used. SOD activities of all 158 isolates were measured and were divided into three groups: high-SOD activity (>0.22, n = 2), moderate-SOD activity (0.15 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Except for colonization, SOD expression is crucial for bacterial growth and survival primarily in the host microenvironment with a high intensity of oxidative stress [128]. Furthermore, there is a relationship between SOD activity and the onset and progress of gastric diseases [129].…”
Section: Superoxidase Dismutasementioning
confidence: 99%
“…Except for colonization, SOD expression is crucial for bacterial growth and survival primarily in the host microenvironment with a high intensity of oxidative stress [128]. Furthermore, there is a relationship between SOD activity and the onset and progress of gastric diseases [129].…”
Section: Superoxidase Dismutasementioning
confidence: 99%
“…Moreover, it has been reported that the enzyme SodB is essential for H. pylori to colonize mice [77], demonstrating that O 2 •− and/or H 2 O 2 are effectively released in vivo and target the bacteria in the gastric mucosa. It has been also shown that the H. pylori strains that are associated with gastric cancer exhibit more SOD activity than those carried by patients with gastritis or gastric and duodenal ulcers, further evidencing that SodB has a major function in the virulence of H. pylori [79]. …”
Section: Resistance Of H Pylori To Oxidative Stressmentioning
confidence: 99%
“…ROS can damage major cellular constituents if the host is unable to quench the free radical overproduction . Both the bacterium and gastric cells respond to oxidative stress by altering the activity of their antioxidant systems. A study showed that H. pylori can interfere with the antioxidant response of the host.…”
Section: Host Factors Implicated In Pathogenesismentioning
confidence: 99%